2023
DOI: 10.2174/1570193x19666220707125726
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Methods and Applications of Bioactive Compounds from Neem (Azadirachta indica): A Mini-Review

Abstract: Neem tree (Azadirachta Indica), native to the Indian subcontinent, is known as a versatile plant, rich source of bioactive compounds such as azadirachtin, nimonol, nimocinol, nimocinolide, gallic acid, gallocatechin, epicatechin, azadiradione, nimbin, salannin, epoxyazadiradione, etc. The isolated from neem phytochemicals, among other, are more than 300. The present work details the techniques for extracting compounds from different parts of neem, such as bark, husk seed, seed, seeds oil, tree, leaves, and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…A similar study was conducted by (Daramola et al, 2023) where botanical extracts of garlic, tulsi, neem, hena, and melia completely inhibited sporulation of F. oxysporum, F. solani, Colletotrichum coccodes, and Alternaria solani. Similar results were reported by previous researchers (Anuradha et al, 2023;Arman et al, 2023;de Alba et al, 2023;Ibiam et al, 2023;Xue et al, 2023) Neem extract and garlic exhibited better efficacy against F. oxysporum growth at concentrations of 5%, 10%, and 15%. The concluding results of the current investigation align with the research of (Ahamed et al, 2017) who evaluated the effects of extracts from five medicinal plants against F. oxysporum in vitro and found that A. indica exhibited the best performance at higher concentrations.…”
Section: Growth Performance Of Fusarium Oxysporum In Response To Bota...supporting
confidence: 90%
“…A similar study was conducted by (Daramola et al, 2023) where botanical extracts of garlic, tulsi, neem, hena, and melia completely inhibited sporulation of F. oxysporum, F. solani, Colletotrichum coccodes, and Alternaria solani. Similar results were reported by previous researchers (Anuradha et al, 2023;Arman et al, 2023;de Alba et al, 2023;Ibiam et al, 2023;Xue et al, 2023) Neem extract and garlic exhibited better efficacy against F. oxysporum growth at concentrations of 5%, 10%, and 15%. The concluding results of the current investigation align with the research of (Ahamed et al, 2017) who evaluated the effects of extracts from five medicinal plants against F. oxysporum in vitro and found that A. indica exhibited the best performance at higher concentrations.…”
Section: Growth Performance Of Fusarium Oxysporum In Response To Bota...supporting
confidence: 90%
“…The leaf powder was boiled in sterilized water for 15 minutes by keeping it in the water bath (10g/100ml). The liquid thus obtained was filtered using Whatman paper 26 .…”
Section: Materials and Methods: Collection Of Leavesmentioning
confidence: 99%
“…However, many other herbs that are of scientific interest still demand description and further studies. Techniques and extracts are constantly being studied for different plant species, but each plant and each type of extract, such as lipophilic oils, peptides, polysaccharides, or antioxidants, all have particularities of chemical extraction processes, which brings complexity to the matter [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%